Heterogeneity and Dynamics of Vasculature in the Endocrine System During Aging and Disease - Stucker, Sina; De Angelis, Jessica; Kusumbe, Anjali P. (Frontiers in Physiology, 2021)
The endocrine system consists of several highly vascularized glands that produce and secrete hormones to maintain body homeostasis and regulate a range of bodily functions and processes, including growth, metabolism and development. The dense and highly vascularized capillary network functions as the main transport system for hormones and regulatory factors to enable efficient endocrine function. The specialized capillary types provide the microenvironments to support stem and progenitor cells, by regulating their survival, maintenance and differentiation. Moreover, the vasculature interacts with endocrine cells supporting their endocrine function. However, the structure and niche function of vasculature in endocrine tissues remain poorly understood. Aging and endocrine disorders are associated with vascular perturbations. Understanding the cellular and molecular cues driving the disease, and age-related vascular perturbations hold potential to manage or even treat endocrine disorders and comorbidities associated with aging. This review aims to describe the structure and niche functions of the vasculature in various endocrine glands and define the vascular changes in aging and endocrine disorders.